1950
DOI: 10.1098/rspa.1950.0036
|View full text |Cite
|
Sign up to set email alerts
|

Electronic wave functions - I. A general method of calculation for the stationary states of any molecular system

Abstract: This communication deals with the general theory of obtaining numerical electronic wave functions for the stationary states of atoms and molecules. It is shown that by taking Gaussian functions, and functions derived from these by differentiation with respect to the parameters, complete systems of functions can be constructed appropriate to any molecular problem, and that all the necessary integrals can be explicitly evaluated. These can be used in connexion with the molecular orbital method, or localized bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,082 publications
(154 citation statements)
references
References 4 publications
1
149
0
4
Order By: Relevance
“…5 STFs behave similarly to hydrogen-like radial functions and are efficient in representing the AOs, but they are difficult to use in calculating threeand four-center two-electron integrals. Boys 6 started to use Gaussian-type orbitals or more properly Gaussian-type functions (GTFs), which differ from the STFs in the exponent term. When the same number of functions are used in linear least-squares fittings, the GTFs are less accurate than the STFs because they decay too fast when compared with the "real" radial functions (e.g., hydrogen-like orbitals).…”
Section: Introductionmentioning
confidence: 99%
“…5 STFs behave similarly to hydrogen-like radial functions and are efficient in representing the AOs, but they are difficult to use in calculating threeand four-center two-electron integrals. Boys 6 started to use Gaussian-type orbitals or more properly Gaussian-type functions (GTFs), which differ from the STFs in the exponent term. When the same number of functions are used in linear least-squares fittings, the GTFs are less accurate than the STFs because they decay too fast when compared with the "real" radial functions (e.g., hydrogen-like orbitals).…”
Section: Introductionmentioning
confidence: 99%
“…The primitive integrals can be evaluated analytically as originally shown by Boys. 12 Since Boys' seminal work, numerous computational approaches have been developed to minimize the effort in this N 4 bottleneck. [13][14][15][16][17] However, even if the most efficient algorithm is being used, the twoelectron integral evaluation phase still takes much of the computation time.…”
Section: Two-electron Repulsion Integralsmentioning
confidence: 99%
“…It was already apparent in the 1950s that calculations of polyatomic systems based on Slater-type orbitals would be intractable. The breakthrough occurred when Boys proposed basis functions based on Cartesian Gaussian functions [4]. It was also found that linear combinations of Gaussians, designated as contracted Gaussians, could approximate atomic orbitals with great accuracy.…”
Section: Introductionmentioning
confidence: 99%